Pembuatan Hidrogel Berbasis Mikrokristal Selulosa Daun Nanas (Ananas comosus L. Merr) dengan Variasi Volume Glutaraldehid - Muhammad Gunawan; Nanda Lestari (Jurnal Indah Sains dan Klinis, 2020)
Pineapple leaves natural fibers contain lignin, hemicellulose, and cellulose. The cellulose content of pineapple leaves is around 69.5% -71.5%. Cellulose-derived microcrystals can be used in the pharmaceutical field as binders in tableting formulations. The research objective was to determine whether pineapple leaves can produce microcrystals, microcrystals can be used in the manufacture of hydrogels and to determine variations in the volume of glutaraldehyde that can affect hydrogels. Experimetal researchbegan with delignification with 4% NaOH, immersed for 1 hour and heated, washed with distilled water until neutral pH and blended with 2.7% NaOH, 7.9% acetic acid, NaOCl until white, heated, the residue was taken and drained. , soaked in 1 N HCl, reheatedfor 2 hours, re-stirred and blended until smooth. Cellulose hydrogel was dissolved in 8.5% NaOH and added with glutaraldehyde in various volume variations. Cellulose and hydrogel microcrystals were characterized by visual, swelling ratio test, FTIR, SEM and XRD. The yield of microcrystalline cellulose was 22%, white, homogeneous. Cellulose and hydrogel microcrystals contain O-H (3800-2700 cm-1), C-H (3000-2850 cm-1) and C-O (1300-800 cm-1) groups. Microcrystalline cellulose can be made from pineapple leaves, hydrogel formation is influenced by variations in the volume of glutaradehydeand the highest and lowest swelling ratios are 400% and 12.5%, respectively.